Koshchei in hell ebook - Mignola, Mike (Koshchei in Hell (2022), 2023)
The world above may be over, and Hellboy gone with it, but Koshchei is still in Hell content with his wine and his books—until an old face arrives and brings Koshchei a critical task.An old and powerful foe is returning, and Koshchei must take up his sword and defend the city from destruction.Mignola returns to Hell to reunite with one of his favorite collaborators, Ben Stenbeck (Frankenstein Underground, Witchfinder: In The Service of Angels, Baltimore, Koshchei the Deathless).Collects Koshchei in Hell #1-#4, Sir Edward Grey: Acheron one-shot, and bonus material.